ANALISIS KAIDAH MUBTADA’ DAN HIKMAH BAGI KEHIDUPAN - Tasya Nadira; M Yusri Ali Lubis (Jurnal Sathar, 2025)
This study aims to investigate the principle of mubtada in nahwu science and explore the lessons that can be learned from its use in everyday life. Mubtada is a crucial part in the composition of nominal sentences in Arabic, functioning as the main subject and must comply with certain requirements such as being in the form of isim and ma'rifah. In addition to being an element of language structure, mubtada also contains meanings that indicate order in thinking, clarity of intent, and responsibility in communicating. This research method uses a qualitative approach with a literature study method. Data were obtained from various classical nahwu books, Al-Qur'an interpretations, and relevant academic literature. The analysis was carried out descriptively, focusing on the requirements of mubtada, variations in existing forms, and the philosophical meanings contained therein. The results of this study indicate that understanding the principle of mubtada can help form an orderly and critical mindset. This reminds us that every individual has a responsibility to convey the truth with a clear structure and precise purpose. Therefore, studying these rules not only deepens the mastery of Arabic, but also instills life values ​​that can be applied widely.